2023
DOI: 10.1186/s12933-023-01919-z
|View full text |Cite
|
Sign up to set email alerts
|

The triglyceride-glucose index is associated with atherosclerosis in patients with symptomatic coronary artery disease, regardless of diabetes mellitus and hyperlipidaemia

Jiao Li,
Zixian Dong,
Hao Wu
et al.

Abstract: Background Diabetes and hyperlipidaemia are both risk factors for coronary artery disease, and both are associated with a high triglyceride-glucose index (TyG index). The TyG index has been presented as a marker of insulin resistance (IR). Its utility in predicting and detecting cardiovascular disease has been reported. However, few studies have found it to be a helpful marker of atherosclerosis in patients with symptomatic coronary artery disease (CAD). The purpose of this study was to demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…Therefore, we selected new-onset CAD patients as our study object to avoid the prevalence-incidence bias as far as possible. Consistent with the previous study [ 37 ], the present study confirmed the TyG index was a risk factor for new-onset CAD. In addition, our study demonstrated that the TyG index was not correlated with new-onset CAD severity, regardless of glucose metabolic states.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, we selected new-onset CAD patients as our study object to avoid the prevalence-incidence bias as far as possible. Consistent with the previous study [ 37 ], the present study confirmed the TyG index was a risk factor for new-onset CAD. In addition, our study demonstrated that the TyG index was not correlated with new-onset CAD severity, regardless of glucose metabolic states.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the emerging TyG index has been noted to be associated with the presence of IS or coronary adverse cardiovascular events in previous studies (38)(39)(40)(41). In addition, the association between elevated TyG index and vulnerable carotid plaque had also been noted (3,23,42). We found a correlation between the TyG index and the incidence of stroke events in T2DM patients (OR: 2.324, 95% CI: 1.256-4.300).…”
Section: A B Csupporting
confidence: 70%
“…The triglyceride (TG)-glucose (TyG) index is the logarithmic product of the circulating fasting TG and glucose concentrations, and has been demonstrated to represent a simple marker for the assessment of IR [ 10 ]. Previous research has shown a significant association between a high TyG index and a higher risk of cardiovascular events [ 11 ]. Although prior studies have separately explored the associations of TyG and BP with CVD, there have been few studies of their cumulative combined effects.…”
Section: Introductionmentioning
confidence: 99%